The effect of avocado consumption on salivary pH among students with halitosis - Maria, Vonny; Annisa, Yinka Mutiara; Erawati, Suci; Daryono, Daryono (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Halitosis is an oral health problem frequently associated with salivary condition, particularly its degree of acidity (pH). Acidic salivary pH supports the growth of anaerobic bacteria which produce volatile sulphur compounds, the primary cause of oral malodour. A non-pharmacological approach with the potential to neutralise salivary pH is the use of natural substances, such as avocado fruit (Persea americana), which contains bioactive compounds with antibacterial and acid-buffering effects. This study aimed to determine the effect of avocado consumption on salivary pH in students with halitosis. A quasi-experimental design with a one-group pretest-posttest model was employed. The sample consisted of 38 students meeting the inclusion criteria of having acidic salivary pH and halitosis. Salivary pH was measured before intervention, and at 30 and 60 minutes after subjects chewed 10 grams of avocado 32 times. Data were analysed using the Friedman and Wilcoxon tests with a significance level of 5%. The results demonstrated a significant increase in salivary pH 30 minutes after avocado consumption, from an acidic towards a neutral state (p < 0.05). However, at the 60-minute measurement, salivary pH returned to baseline and showed no significant difference compared to pre-intervention values (p > 0.05). This indicates that the effect of avocado consumption on increasing salivary pH is transient. In conclusion, consuming avocado fruit can significantly increase salivary pH in the short term and may help reduce halitosis, although regular consumption coupled with diligent oral hygiene practices is necessary to maintain this effect.